2017
DOI: 10.1155/2017/3763607
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Useful Plants in the Catchment Area of the Proposed Ntabelanga Dam in the Eastern Cape Province, South Africa

Abstract: Background The developmental projects, particularly construction of dams, result in permanent changes of terrestrial ecosystems through inundation. Objective The present study was undertaken aiming at documenting useful plant species in Ntabelanga dam catchment area that will be impacted by the construction of the proposed dam. Methods A total of 55 randomly selected quadrats were used to assess plant species diversity and composition. Participatory rural appraisal (PRA) methods were used to identify useful pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 22 publications
2
9
0
Order By: Relevance
“…Such a perception was observed by dos Santos et al (2014) who argued that there is often no differentiation by local communities between invasive alien species and native species as local communities often focus on the ecosystem goods and services provided by such species. Research findings from the current investigation corroborate previous studies which showed that invasive alien plant species may also have positive socio-economic benefits (Zimmermann and Neser 1999;Njoroge et al 2004;Bigirimana et al 2011Bigirimana et al , 2012Semenya et al 2012a,b;Maroyi 2017aMaroyi ,b, 2018Semenya and Maroyi 2018). Borokini and Babalola (2012) argued that economic exploitation of invasive alien species is usually labor intensive and menial jobs are usually created while providing additional means of income for local communities.…”
Section: Perceptions and Utilization Of O Ficus-indicasupporting
confidence: 89%
“…Such a perception was observed by dos Santos et al (2014) who argued that there is often no differentiation by local communities between invasive alien species and native species as local communities often focus on the ecosystem goods and services provided by such species. Research findings from the current investigation corroborate previous studies which showed that invasive alien plant species may also have positive socio-economic benefits (Zimmermann and Neser 1999;Njoroge et al 2004;Bigirimana et al 2011Bigirimana et al , 2012Semenya et al 2012a,b;Maroyi 2017aMaroyi ,b, 2018Semenya and Maroyi 2018). Borokini and Babalola (2012) argued that economic exploitation of invasive alien species is usually labor intensive and menial jobs are usually created while providing additional means of income for local communities.…”
Section: Perceptions and Utilization Of O Ficus-indicasupporting
confidence: 89%
“…Generally, most fruit species are accessible in the summer, i.e., hot-dry season, which is often associated with the scarcity of food supplies (Table 3). For some of the plants, the fruiting period indicated by the participants aligns with the existing evidence in the literature [5,[46][47][48][49][50][51]. On the other hand, the extended fruiting duration reported for plants such as Englerophytum magalismontanum, Ficus sur, and Ficus thonningii was in contrast to shorter duration reported in literature (Table 3).…”
Section: Seasonal Availability and Occurrence Of Fruits In The Study Areasupporting
confidence: 78%
“…Even though the abundance of indigenous plants, especially fruits, is generally well acknowledged in sub-Saharan Africa, the documentation of their uses and associated local knowledge remain inadequate [4,13,23]. This is further worsened by the potential loss of valuable local fruit trees due to diverse threats, particularly habitat loss arising from anthropogenic factors [11,51]. The current findings established the rich, indigenous knowledge of local fruit species among participants in the study area.…”
Section: Implication Of Current Findings For Food and Nutritional Securitymentioning
confidence: 64%
“…Study site 3 is situated in the former Ciskei homeland while study sites 1 and 2 are situated in the former Transkei homeland. Research by Maroyi (2017b) showed that annual rainfall ranges from 800 mm to 1200 mm while annual temperature ranges from 13°C to 22°C in Elundini Local Municipality (study site 1). The Mbhashe Local Municipality (study sites 2) is located in a climatic transition zone between the temperate south coast and the subtropical north coast of South Africa with average annual rainfall of 1069 mm, average winter and summer temperatures of 21.5°C and 24°C, respectively (Maroyi 2017a).…”
Section: Study Areamentioning
confidence: 96%